Online project-based learning for ESP: Determinants of learning outcomes during Covid-19 - Akhmad Habibi; Yasir Riady; Turki Mesfer Alqahtani; Ahmad Rifki; Nour Awni Albelbisi; Muhammad Fauzan; Habizar Habizar (Universitas Syiah Kuala, 2022)
Evaluating the learning outcomes of a certain course implementation can improve the quality of education. This study is focused on Indonesian EFL undergraduates’ perceptions of the relationships between teacher performance, technological resources, online project-based learning (OPJBL), and ESP learning outcomes. Participants of the study have attended English for specific purposes (ESP) online courses during school closures due to Covid-19. A survey was addressed to 350 undergraduates after a one-semester implementation of the OPJBL. The students were requested to rate their perceptions on validated items using a 7-point Likert-type scale for the data collection. The data were modelled and computed through partial least square structural equation modelling (PLS-SEM). The main findings of the study revealed that teacher performance and technological resources were significant in predicting OPJBL. Similarly, OPJBL was found to play a significant role in affecting ESP learning outcomes. Teacher performance and technological resources were also correlated to ESP learning outcomes. Significant differences were found among students’ locations for all variables. The findings highlight the benefits of the SEM approach for establishing the proposed framework and assessing the links between variables concerning the OPJBL and learning outcomes.